Foundations of Second Language Acquisition: Strategies and Motivation of Banjarese Young Learners in Learning English as a Foreign Language - Ali Kasan, Rusnadi; Fadillah, Ridha; Yusuf, Muhammad (LET: Linguistics, Literature and English Teaching Journal, 2019)
The study examined the language learning strategies and motivations of EFL learners in Banjarmasin Junior High Schools, South Kalimantan, Indonesia. The researchers used a mixed-method approach, collecting data from 60 student participants across 3 State Islamic Junior High Schools and 3 State Junior High Schools in the region. The data were gathered through a survey questionnaire and semi-structured interviews. The quantitative data were analyzed using SPSS to identify the preferred strategies and levels of motivation. The qualitative data were analyzed using thematic analysis to gain insights into the learners' strategy use and motivations. The findings reveal that the participants utilized a variety of language learning strategies, such as cognitive, metacognitive, social, and affective strategies, to acquire and learn English. The participants were found to be both integratively and instrumentally motivated to learn English, driven by a desire to integrate with the target language community as well as practical reasons, like academic and career prospects. The study offers valuable insights into the language learning behaviors and motivations of young Banjarese EFL learners, which can inform more effective English language teaching and learning practices in the region.